2019
DOI: 10.1002/aenm.201803422
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Ion Conducting Electrolyte Based on Electrospun Nanofibers for High‐Performance Lithium Batteries

Abstract: Herein, a novel electrospun single‐ion conducting polymer electrolyte (SIPE) composed of nanoscale mixed poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) and lithium poly(4,4′‐diaminodiphenylsulfone, bis(4‐carbonyl benzene sulfonyl)imide) (LiPSI) is reported, which simultaneously overcomes the drawbacks of the polyolefin‐based separator (low porosity and poor electrolyte wettability and thermal dimensional stability) and the LiPF6 salt (poor thermal stability and moisture sensitivity). The electrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 49 publications
4
92
0
Order By: Relevance
“…Similarly, Qin et al 133 synthesized and investigated polyborate-based electrolytes offering high ionic conductivity (1.8 × 10 −4 S cm −1 at 30°C) upon incorporation of a mixture of EC and DMC. Comparable results were obtained by Li et al 134 for the electrospun polyIJdiaminodiphenylsulfone)-type electrolyte. Noteworthy, however, all these systems provide Li + transference numbers (t + ) below 0.9 and require the incorporation of additional polymers like highly dielectric polyIJvinylidene difluoride) (PVdF) or its hexafluoropropylene-copolymer to realize suitable mechanical properties.…”
Section: C) Realization Of Anisotropic Conduction Pathwayssupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly, Qin et al 133 synthesized and investigated polyborate-based electrolytes offering high ionic conductivity (1.8 × 10 −4 S cm −1 at 30°C) upon incorporation of a mixture of EC and DMC. Comparable results were obtained by Li et al 134 for the electrospun polyIJdiaminodiphenylsulfone)-type electrolyte. Noteworthy, however, all these systems provide Li + transference numbers (t + ) below 0.9 and require the incorporation of additional polymers like highly dielectric polyIJvinylidene difluoride) (PVdF) or its hexafluoropropylene-copolymer to realize suitable mechanical properties.…”
Section: C) Realization Of Anisotropic Conduction Pathwayssupporting
confidence: 66%
“…Nonetheless, one severe constraint remained: the electrochemical (in-)stability towards oxidation, limiting the application of such polymer electrolytes to LiFePO 4 as the cathode active material. [131][132][133][134][135] This limitation has been overcome only very recently by Nguyen et al, 136 who synthesized multi-block co-polyIJarylene ether sulfone) single-ion conductors based on alternating ionophobic and ionophilic blocks. The resulting films are self-standing and nanophase-separated.…”
Section: C) Realization Of Anisotropic Conduction Pathwaysmentioning
confidence: 99%
“…[257] Zhang et al reported that FEC is firstly reduced by Li metal in an electrolyte composed of LiPF 6 and EC/DEC. [258,259] Both the reduction of LiFSI and FEC led to the formation of a LiF-rich layer, which effectively improved the battery performance. [257][258][259] To make LT batteries, it is critical to design electrolyte|electrode interfaces characterized by a low impedance.…”
Section: Electrochemical Stability and Interfacial Stabilitymentioning
confidence: 99%
“…[258,259] Both the reduction of LiFSI and FEC led to the formation of a LiF-rich layer, which effectively improved the battery performance. [257][258][259] To make LT batteries, it is critical to design electrolyte|electrode interfaces characterized by a low impedance. Introducing Li salts that form ionically conductive SEIs may be conducive to that.…”
Section: Electrochemical Stability and Interfacial Stabilitymentioning
confidence: 99%
“…The electrochemical devices including fuel cells, secondary battery,, and supercapacitor become attractive because they are sustainable and eco‐friendly. Especially the fuel cells are high‐energy conversion efficiency devices with great prospects for future energy needs in view of zero emission of pollutants.…”
Section: Introductionmentioning
confidence: 99%